Analysis of some morphological characters of Elzunia Bryk, 1937 (Nymphalidae: Danainae: Ithomiini) results in a revised classification - Crom, Jean François Le; Ávalos-Hernández, Omar; Winhard, Walter; Andrade-C., M. Gonzalo; Llorente-Bousquets, Jorge (Zootaxa, 2018)
We propose a revised classification for the genus Elzunia Bryk, 1937, with four species and 20 subspecies. We describe two new subspecies, Elzunia humboldt carlosi Le Crom and Llorente, ssp. nov., and Elzunia humboldt willmotti Le Crom, Llorente and Andrade, ssp. nov. We recognize five additional unnamed subspecies but do not describe them because they are represented by too little material. A detailed examination of 854 specimens from 31 collections allowed us to define 24 stable phenotypes and delimit their geographic distribution. We present a diagnosis and description for each taxon and provide images of the wing coloration pattern and male genitalia, and a distribution map. We also present a key for all the species and subspecies. We conducted a multivariate statistical analysis of measurements of the discal cell (DC) veins, and with this we explore the species groupings by these characters. Lastly, we discuss mimetic interactions of this genus with species of other Ithomiini and Heliconiinae.